2006
DOI: 10.1038/ng1933
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding the synaptic scaffolding protein SHANK3 are associated with autism spectrum disorders

Abstract: SHANK3 (also known as ProSAP2) regulates the structural organization of dendritic spines and is a binding partner of neuroligins; genes encoding neuroligins are mutated in autism and Asperger syndrome. Here, we report that a mutation of a single copy of SHANK3 on chromosome 22q13 can result in language and/or social communication disorders. These mutations concern only a small number of individuals, but they shed light on one gene dosage-sensitive synaptic pathway that is involved in autism spectrum disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
1,240
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,395 publications
(1,306 citation statements)
references
References 16 publications
35
1,240
0
12
Order By: Relevance
“…Furthermore, autism-linked mutations (R12C, arginine to cysteine; L68P, leucine to proline) 168,171,172 in SHANK3 impaired its integrin inhibitory function in non-neuronal cells 170 prompting a new intriguing proposal that at least some of the SHANK ASD-associated mutations alter the integrin activation in neurons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, autism-linked mutations (R12C, arginine to cysteine; L68P, leucine to proline) 168,171,172 in SHANK3 impaired its integrin inhibitory function in non-neuronal cells 170 prompting a new intriguing proposal that at least some of the SHANK ASD-associated mutations alter the integrin activation in neurons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, some exons are particularly large, so 36 amplicons were utilized to amplify the coding sequences and about 100-150 base pairs deep in the intron (see Supplementary Table S1 for primer sequences and amplicon length). In order to amplify some of these amplicons, we used the primer sequences reported by Durand et al, 14 whereas we used Primer 3 Input (http://frodo.wi.mit.edu/primer3/) to design the primers for those amplicons that we had to adapt to DHPLC parameters. We were not able to amplify exons 1 and 11, because of their high-GC content.…”
Section: Patients and Controlsmentioning
confidence: 99%
“…[11][12][13] Overall, identified genetic causes of autism can be classified as cytogenetically visible chromosomal abnormalities (B5%), copy number variants (10-20%), and single-gene disorders (B5%). 13 Molecular analyses have highlighted the role of point mutations in single genes located in some of these regions: SHANK3 (ProSAP2) on chromosome 22q13, [14][15][16][17] Neuroligin 3 (NLGN3) and Neuroligin 4 (NLGN4) on the X chromosome, 18 Neurexin 1 (NRXN1) on chromosome 2p16, [19][20][21] and Contactin Associated Protein-like 2 (CNTNAP2) on chromosome 7q35. [22][23][24] Notably, both neuroligin and neurexin proteins have key roles in the formation and functioning of synapses, particularly the alignment and activation of glutamate and GABA synapses.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of variations in neuroligin genes ( NLGN4X and NLGN3X ) in patients with ASD suggested that proteins involved in synapse formation and synaptic transmission play an important role in the etiology of ASD (Jamain et al., 2003). Similarly, rare variations have been detected in genes coding for ion channels (e.g., CACNA1 and CACNB2 ), as well as proteins involved in synaptic structure, gene transcription, and chromatin remodeling (e.g., NRXN1 , CTTNBP2, CHD8, and SHANK3 ), indicating that altered synaptic plasticity and regulation of gene expression may also be involved in the etiology of ASD (Cross‐Disorder Group of the Psychiatric Genomics Consortium, 2013; De Rubeis et al., 2014; Durand et al., 2007). …”
Section: Introductionmentioning
confidence: 99%